Is the longstanding local rice cultivar “X-Jigna” being replaced by the improved variety “Shaga” in fogera plain, Northwest Ethiopia? - Adane Melak Beyene; Ayele Tesfahun Gashu; Misganaw Anteneh Tegegne; Atrsaw Anteneh Mihertie (Cogent Economics & Finance)
This study investigates how far and by what factors the local rice cultivar X-Jigna is being replaced by the improved variety Shaga in the Fogera plain, Ethiopia. It applied a mixed-method research design. The explanatory method was used to analyze qualitative data, while simple descriptive and inferential statistics were used to analyze quantitative data. As a result, the adoption level of improved rice varieties was found to be too low (15%), while the vast majority of rice-growing households used X-Jigna. However, the explanatory analysis highlighted that Shaga outperforms X-Jigna in resilience to diseases and shattering, higher grain yield, and softness of injera and flour density traits. Consequently, its percentage share of area coverage increased from 1 to 12, while X-Jigna’s decreased from 95 to 84 within a short time. This phenomenon demonstrates great strides have been made in replacing X-Jigna with Shaga. Based on the results of logistic regression analysis, age, educational background, and experience in rice cultivation of household heads, land-owned size, and road and credit access significantly influence adoption decisions. Therefore, it is suggested that offering youth-oriented extension services, expanding education services, improving road infrastructure, and reducing bureaucracy in credit services are areas to be emphasized to improve adoption.